Fatigue and Depression in Sick‐Listed Chronic Low Back Pain Patients. Issue 7 (9th April 2014) - Snekkevik, Hildegun; Eriksen, Hege R.; Tangen, Tone; Chalder, Trudie; Reme, Silje E.
Abstract Objective The relationship between fatigue and pain has been investigated previously, but little is known about the prevalence of substantial fatigue in patients sick‐listed for chronic low back pain (CLBP) and about how fatigue is associated with depression, pain, and long‐term disability. The aims of the study were to examine the prevalence of substantial fatigue; associations between fatigue, depression, and pain; and whether fatigue predicted long‐term disability. Methods Five hundred sixty‐nine patients participating in a randomized controlled trial and sick‐listed 2–10 months for LBP were included in the study. Cross‐sectional analyses were conducted to investigate the prevalence and independent associations between fatigue, depression, pain, and disability, while longitudinal analyses were done to investigate the association between fatigue and long‐term disability. Results The prevalence of substantial fatigue was 69.7%. Women reported significantly more fatigue than men (t = −3.6, df = 551; P < .001). Those with substantial fatigue had higher pain intensity (t = −3.3, df = 534; P = 0.01), more depressive symptoms (t = −10.9, df = 454; P < 0.001), and more disability (t = −7.6, df = 539; P < 0.001) than those without substantial fatigue. Musculoskeletal pain and depression were independently associated with substantial fatigue. In the longitudinal analyses, fatigue predicted long‐term disability at 3, 6, and 12 months' follow‐up. After pain and depression were controlled for, fatigue remained a significant predictor of disability at 6 months' follow‐up. Conclusions The vast majority of the sick‐listed CLBP patients reported substantial fatigue. Those with substantial fatigue had more pain and depressive symptoms and a significant risk of reporting more disability at 3, 6, and 12 months. Substantial fatigue is disabling in itself but also involves a risk of developing chronic fatigue syndrome and long‐term disability.